Growth of barium oxalate crystals in agar-agar gel and their characterization - Dalai, P. V.; Saraf, K. B.; Shah, S. (Crystal Research and Technology, 2009)
{Single crystals of barium oxalate have been grown by get method using agar-agar gel as media of growth at ambient temperature. The optimum conditions were established by varying various parameters such as concentration of gel, concentration of reactant, gel setting time etc. Prismatic platy shaped transparent crystals were obtained. The grown crystals were characterized through powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) studies, Thermogravimetric (TGA) and Differential thermal analysis (DTA). The compound crystallizes under monoclinic structure with lattice parameters a = 6.6562 angstrom
Keywords: barium oxalate; Crystal growth; FT-IR; TGA/DTA; XRD